The effects of an 8-week French Contrast Training program on lower limb strength and power in elite martial arts athletes - Chen, Hao; Zhao, Ziren; Zheng, Xin; Cao, Liquan; Du, Jingtao; Yu, Zhongtao (Frontiers in Sports and Active Living, 2025)
BackgroundLower limb strength and power are critical for martial arts athletes to perform complex movements such as aerial outward swings. French Contrast Training (FCT), which integrates heavy compound exercises, plyometrics, and assisted plyometric movements into a single session, has been proposed to elicit superior neuromuscular adaptations. However, the effectiveness of FCT in elite martial arts athletes remains unclear.ObjectiveThis study aimed to investigate the effects of an 8-week FCT program on lower limb strength and power in elite martial arts athletes.MethodsIn total, 24 elite male martial arts athletes were randomly assigned to the FCT group (n = 12) or the control group (n = 12). Both groups completed an 8-week (twice a week) training program. The FCT protocol included the following four sequential exercises per session: 85% one-repetition maximum (1RM) back squats, countermovement jumps (CMJs), 30% 1RM squat jumps (SJs), and band-assisted jumps. The control group performed traditional resistance training for the same muscle groups. The pre- and post-intervention assessments included isometric mid-thigh pulls [IMTPs; maximal force output (MFO), relative MFO, and rate of force development (RFD)], CMJs, SJs with jump height, peak power output (PPO), and mean power output (MPO), elasticity index (EI), and dynamic strength index (DSI). All the data were analyzed using the linear mixed model. Effect sizes were calculated using Cohen's d. Statistical significance was set at p < 0.05.ResultsThe FCT group showed significantly greater improvements than the control group in IMTP (MFO: p < 0.001, d = 1.66; relative MFO: p = 0.001, d = 1.51; RFD: p = 0.001, d = 1.52), CMJ (jump height: p = 0.011, d = 1.14; PPO: p < 0.001, d = 1.61; MPO: p = 0.013, d = 1.11), SJ (jump height: p = 0.019, d = 1.03; PPO: p = 0.043, d = 0.88; MPO: p < 0.001, d = 1.63), EI (p = 0.521, d = −0.27), and DSI (p < 0.001, d = 2.07). No adverse events were reported.ConclusionsThis study provides preliminary evidence that French Contrast Training effectively enhances lower body strength and power in elite martial arts athletes.